Age-Associated Risk of Liver-Related Adverse Drug Reactions - Han, Yan-zhong; Guo, Yu-ming; Xiong, Peng; Ge, Fei-lin; Jing, Jing; Niu, Ming; Zhao, Xu; Bai, Zhao-fang; Song, Hai-bo; Xiao, Xiao-he; Wang, Jia-bo (Frontiers in Medicine, 2022)
Objective: Aging population is generally considered more sensitive to adverse drug reactions (ADRs). Yet big data-based quantitative evidence currently does not exist to support this concept. This study aims to investigate age-associated risks of liver-related ADR (L-ADR). Methods: Spontaneous reporting data from 2012 to 2016 was retrieved from the China National ADR Monitoring System. The risk ratio (RR) was used to quantify the relative risk of L-ADR of each age group. The reporting odd ratio (ROR) was used to quantify the correlation with the risk of L-ADR of each drug category or drug in older adults. Results: Totally 64,702 L-ADR reports were retrieved, covering ages from 1 to 116, with a median age of 49. The RR values increased exponentially with the increase of age, which indicates that the relative risk of L-ADR increased by 33% for every 10 years increase in age. The age cutoff point for relative high-risk of L-ADR was estimated at 52.0 years old (RR =1). In 17 categories composed of 270 drugs, the top 3 drug categories with high correlation to the risk of L-ADR in older adults were antiarrhythmic (ROR, 5.75; 95% CI: 4.45-7.42), antilipemic (ROR, 4.77; 95% CI: 4.53-5.02) and antihypertensive (ROR, 2.97; 95% CI: 2.59-3.41). Conclusions: This research illustrates quantitatively that aging is a potential risk factor for L-ADR, with a 33% increase in relative risk for every 10 years increase in age. Risk management should be addressed for older adults when those drugs with high correlation to the risk of L-ADR are used.